Exploring Transition to Self-Management Within the Culture of Sickle Cell Disease. (January 2017) - Labore, Nancy; Mawn, Barbara; Dixon, Jane; Andemariam, Biree
Purpose: The aim of this study was to explore the meaning of transition to self-management in sickle cell disease.Design/Method: Twelve audio-recorded semistructured interviews were conducted with a sample of 21- to 25-year-olds recruited from a comprehensive sickle cell center in the northeast region of the United States. Data were analyzed using an existential framework according to van Manen's phenomenological method.Findings: The meaning of transition to self-management was found in lived time, space, body, and human relationship. The emerging themes highlighted in this article include: Best Mother Ever, Growing up in the Hospital, I'm Not Trying that Again, Doing it on My Own, Living Day-by-Day, and Not a Kid any Longer. The themes reflected meaning and insight into this unique experience.Conclusion/Practice Implications: Study results emphasize the culturally constructed meaning of transition to sickle cell disease self-management and need to integrate transcultural perspectives into nursing practice to support this emerging phenomenon.